Outpatient surgical management of non‐melanoma skin cancers of the head and neck in a regional centre: an analysis of costs and outcomes. Issue 1 (17th November 2020) - Nightingale, James; Travers, Liam; Campbell, Jakob; Huang, Johnson; Green, Megan; Warren, Tim; Fitzgerald, Garret
Abstract : This study presents the novel introduction of an outpatient‐based treatment model for non‐melanoma skin cancer in a regional ear, nose and throat department. Our reporting of non‐melanoma skin cancer lesions, associated margins and outcomes in conjunction with hospital inpatient versus outpatient costs and patient location linked to health service versus local primary care follow‐up, provides a presentation of this novel outpatient model for the consideration of its implementation in future planning and resource allocation. Abstract: Background: Non‐melanoma skin cancer is the most commonly diagnosed malignancy in Australia. Lesions of the head and neck are often outside the scope of primary care providers. The challenges of cancer care in regional Australia necessitate careful resource planning. This study presents an outpatient model that minimizes health service cost with local general practitioner follow‐up. Methods: A retrospective review of 105 patients with 122 skin lesions in a dedicated Facial Lesion Assessment Management and Excision clinic was performed from July 2018 to 2019. Clinical outcomes, patient travel and cost analysis/comparison were recorded. Results: There were 85 malignant cases with 59 basal cell carcinomas and 25 squamous cell carcinomas. For basal cell carcinoma, clear margins (≥3 mm), close margins (<3 mm) and positive margins were achieved in 24 (48%), 23 (46%) and three (6%) cases, respectively. For squamous cell carcinoma, clear margins (≥5 mm), close margins (<5 mm) and positive margins were achieved in seven (38.8%), 11 (61.1%) and none (0%) of the cases, respectively. Complications included one haematoma and two wound infections. For 37% of patients living >100 km from the department, 72.3% had local general practitioner follow‐up. Inpatient cost was 2870, 5697 and 9300 for primary closure, local flap and full‐thickness skin graft, respectively, and outpatient cost was 746 for a single facial lesion. Conclusion: This study presents a cost‐effective model for the management of non‐melanoma skin cancers with improved departmental efficiency and streamlined patient care in an outpatient skin cancer management model in a regional centre.